HD 219666 b: a hot-Neptune from TESS sector 1 - Esposito, Massimiliano; Tala, Marcelo (Astronomy and astrophysics, 2019)
We report on the confirmation and mass determination of a transiting planet orbiting the old and inactive G7 dwarf star HD 219666 (M⋆ = 0.92 ± 0.03 M⊙, R⋆ = 1.03 ± 0.03 R⊙, τ⋆ = 10 ± 2 Gyr). With a mass of Mb = 16.6 ± 1.3 M⊕, a radius of Rb = 4.71 ± 0.17 R⊕, and an orbital period of Porb ≃ 6 days, HD 219666 b is a new member of a rare class of exoplanets: the hot-Neptunes. The Transiting Exoplanet Survey Satellite (TESS) observed HD 219666 (also known as TOI-118) in its Sector 1 and the light curve shows four transit-like events, equally spaced in time. We confirmed the planetary nature of the candidate by gathering precise radial-velocity measurements with the High Accuracy Radial velocity Planet Searcher (HARPS) at ESO 3.6 m. We used the co-added HARPS spectrum to derive the host star fundamental parameters (Teff = 5527 ± 65 K, log g⋆ = 4.40 ± 0.11 (cgs), [Fe/H]= 0.04 ± 0.04 dex, = −5.07 ± 0.03), as well as the abundances of many volatile and refractory elements. The host star brightness (V = 9.9) makes it suitable for further characterisation by means of in-transit spectroscopy. The determination of the planet orbital obliquity, along with the atmosphericmetal-to-hydrogen content and thermal structure could provide us with important clues on the formation mechanisms of this class of objects.
Published online 28 March 2019
Gesehen am 24.05.2019